A tetranuclear nickel(II) complex for water oxidation: Meeting new challenges. (28th January 2019) - Azadi, Gouhar; Zand, Zahra; Mousazade, Younes; Bagheri, Robabeh; Cui, Junfeng; Song, Zhenlun; Bikas, Rahman; Wozniak, Krzysztof; Allakhverdiev, Suleyman I.; Najafpour, Mohammad Mahdi
Abstract: Ni complexes are promising catalysts for water splitting. Herein, a tetranuclear nickel(II) complex with bis-[( E )- N ′-(1-(pyridin-2-yl)ethylidene)]carbohydrazide (HL), was synthesized and characterized by spectroscopic methods and single crystal X-ray analysis. The complex is a tetranuclear complex and the ligands are coordinated to the metal ions in the mono-negative form, (L) - to form a tetranuclear [NiL]4 4+ unit. Each Ni(II) ion is six-coordinated by pyridine nitrogen, azomethine nitrogen and oxygen atoms of two perpendicular carbohydrazone ligands in the mer configuration. The complex was studied as a water-oxidizing catalyst. In the next step, the role of the Ni-based compound for water oxidation on the surface of fluorine doped tin oxide as one of the true catalysts was investigated by scanning transmission electron microscopy, scanning transmission electron microscopy, spectroelectrochemistry, and electrochemistry. The electrode after water oxidation by the complex was studied and a relation between the decomposition of the Ni complex and water-oxidation reaction was proposed. The experiments show that under water-oxidation condition in the presence of the complex, a Ni-based compound on the electrode is a candidate as a contributor to the observed catalysis. Graphical abstract: A tetranuclear nickel(II) complex was synthesized, characterized, and its water-oxidizing activity was investigated. Highlights: A nickel(II) complex was synthesized and characterized. The complex was used as a water-oxidizing catalyst. The role of Ni oxide or uncomplexed Ni ions for water oxidation was investigated.